Green Marketing, Word Of Muth, And Brand Trust On Purchase Decission Coffee Drink - Dewi Murtiningsih; Yananto Mihadi Putra; Firman Fauzi (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
This study aims to determine the: does green marketing influence purchase decission?, does word of mouth influence purchase decission?, does brand trust influence purchase decission?, does green marketing, word of mouth, brand trust influence purchase decission?. The type of research is descriptive association; the sample of this study includes 100 respondents determined by the MLE formula, and researcher use a sample of 110 with the consideration that if there was a defect in the questionnaire then the sample size would still ben fullfilled; the sampling technique is simple random sampling; the data is obtained by distributing a questionnaire and then analyzing it using SPSS Version 26. Green marketing influence purchase decission, word of mouth influence purchase decission, brand trust influence purchase decission; green marketing, word of mouth, brand trust influence purchase decission. Future research is expected to add the number of samples, expand the research object, and add relevant topics; future research is expected to process data with different analysis tools.